2015
DOI: 10.3109/17549507.2014.930175
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering motivators and stumbling blocks: Exploring the clinical research experiences of speech-language pathologists

Abstract: Healthcare providers increasingly expect that allied health staff will not only translate research evidence into their clinical practice, but also generate research. Little is known about how well prepared clinicians are to meet these expectations. Research suggests that allied health professionals, including speech-language pathologists, have moderate levels of interest in research, but only little to moderate experience participating in research activities. The present study aimed to explore the experiences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(38 citation statements)
references
References 16 publications
2
36
0
Order By: Relevance
“…As a result, those without postgraduate degrees may have limited knowledge and experience of research. These findings were consistent with findings in other research where a higher level of academic training was predictive of higher research engagement (Finch et al., ).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…As a result, those without postgraduate degrees may have limited knowledge and experience of research. These findings were consistent with findings in other research where a higher level of academic training was predictive of higher research engagement (Finch et al., ).…”
Section: Discussionsupporting
confidence: 92%
“…As a result, those without postgraduate degrees may have limited knowledge and experience of research. These findings were consistent with findings in other research where a higher level of academic training was predictive of higher research engagement (Finch et al, 2015). Practitioners in this study reported similar barriers and enablers to research as those in other health professions, including nursing, allied health and medicine (Akerjordet et al, 2012;Hiscock et al, 2014;Johnson et al, 2014;Marshall et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations